Measurement of talent in judo using a unique, judo-specific ability test - Lidor, R.; Melnik, Y.; Bilkevitz, A.; Arnon, M.; Falk, B. (The Journal of Sports Medicine and Physical Fitness, 2005)
Aim: Coaches of young athletes at early phases of development often use batteries of tests in order to obtain information that will be helpful in predicting their future success. However, little scientific inquiry has been conducted on the relevance of the testing process to the final selection and success of young prospects. The purpose of this study was to examine the benefits of a unique judo-specific ability test in early phases of talent development and selection. Methods: Ten judokas (12-15 years of age) underwent assessment of general ability and specific judo ability 3 times during 1994 and 1995, at about 6-month intervals. The general ability test included: sit-ups, push-ups, and side-to-side jumps. The specific judo ability test was comprised of 10 stations in which the judokas performed physical ability and skill tasks. Following the 12-month training program the judokas were ranked by the 2 national judo coaches. Eight years after the beginning of the training program, the judokas were ranked once again by the national coaches. Results. Data analysis revealed that the specific judo ability test did not correlate with either the 1995 or with the 2003 ranking. Conclusion: Because the unique judo-specific ability test was not found to be sensitive enough to accurately measure talent, it is suggested that future studies investigate the usefulness of tests reflecting a more open-skill environment.